Exploring the Opportunities for Using Gentle Remediation Options at the Lindholmen Southern Sector in Gothenburg - PRSA GAZILJ, LUCIJA (My University, 2023)
Gentle Remediation Options (GRO) are low-cost and low-impact but sometimestime consuming methods to deal with elevated levels of soil contamination. GRO rely on amendments, plant-, fungi-, and bacteria-based methods and form a subset of naturebased solutions (NBS). The aim of this thesis is to explore the opportunities for using GRO at the Lindholmen 6:9 property (a former shipyard area) that is currently sitting idle awaiting redevelopment for another 10-20 years. The specific objectives to reach this aim are to: i) identify potential soil contaminants at the Lindholmen 6:9 property based on investigation of previous uses of the area; ii) identify potential GRO strategies to deal with these soil contaminants at the Lindholmen 6:9 property; iii) delimit an area of interest and identify GRO strategies of interest for the stakeholder; and iv) review literature on effectiveness of relevant plant species for these strategies of interest. A retrospective study of orthophotos of the property, a review of previous site investigations, a consultation with the Shipyard Historical Association, a review of the Industry list for surveying of contaminated sites, stakeholder consultation and a literature review were used to reach the objectives. The study results suggest phytoextraction and phyto- and rhizodegradation for the removal of identified primary potential contaminants from soils at the delineated area of interest of the Lindholmen 6:9 property – lead as a representative of heavy metals and aliphatic hydrocarbons together with polycyclic aromatic hydrocarbons (PAHs) as organic contaminants, respectively. The identified candidate species for the area of interest are grasses such as ryegrass Lolium perenne, Sorghum Bicolor, Pennisetum sinese, alfalfa Medicago sativa as well as tree species poplar (Populus nigra, Populus deltoides) and willow (Salix matsudana, Salix schwerinii, Salix viminalis, Salix smithiana, Salix purpurea). Lead can however be very difficult to phytoextract as its bioavailability is usually low in the historically contaminated soils. An alternative strategy aimed at reducing mobility of contaminants in soils with help of stabilising plants (phytostabilisation) and/or immobilising soil amendments (chemical stabilisation/immobilisation) could potentially be considered for managing of this contaminant.. Further research is needed to assess the possibility of retaining parking lots in the area of interest during "gentle remediation". Soil sampling and analysis is recommended in accordance with a sampling plan developed in this study. Laboratory or (and) pilot field experiments are necessary to test the effectiveness of the candidate plant species for site-specific conditions before a full-scale field trial.
Keywords: phytoremediation, gentle remediation options, nature- based solutions, contaminated soil, contaminated sites